The gender gap - Seiler, S. (Sportscience, 1997)
The world's fastest women are now getting slower, while the men keep getting faster. That's the outcome of our analysis of top running performances of the last 40 years. Reduced use of anabolic steroids may be the reasonwomen runners are no longer becoming like men. Authors conclude from their research that the fall and rise of the gender performance gap in running is largely a consequence of the rise and fall in the illegal use of performance enhancing drugs from the 60s to the 90s. It is unlikely that drug use has been (or will ever be) eliminated, but it has been reduced.